A manganese porphyrin–α-cyclodextrin conjugate as an artificial enzyme for the catalytic epoxidation of polybutadiene. Issue 44 (16th May 2018) - Zhang, Qi-Wei; Elemans, Johannes A. A. W.; White, Paul B.; Nolte, Roeland J. M.
Abstract : A manganese porphyrin–α-cyclodextrin conjugate was designed as an artificial clamp-like enzyme to catalyze the epoxidation of cis -polybutadiene with trans -epoxide preference. Abstract : We describe a manganese porphyrin–α-cyclodextrin conjugate as a catalyst for the epoxidation of cis -polybutadiene with trans -epoxide preference, which is a reverse stereoselectivity as compared to normal porphyrin catalysts. A clamp-like mechanism is proposed based on a combination of circular dichroism analysis, molecular modeling, and a series of epoxidation experiments.